Analysis of the Antioxidant Activity of Strawberry Kombucha using the UV–Vis Spectrophotometric Method - Esati, Ni Ketut; Lestari, Gusti Ayu Dewi; Griadnyana, Ida Bagus Nanda (Universitas Nusa Cendana, 2025)
The development of modern lifestyles, which tend to favor instant foods and beverages, has increased the risk of degenerative diseases associated with oxidative stress. This condition has driven the demand for foods and beverages rich in antioxidants. Kombucha is a fermented beverage recognized for its probiotic and antioxidant properties, while strawberries are rich in natural antioxidant compounds. The combination of these two components has the potential to produce a functional beverage beneficial to health, particularly as a source of antioxidants. Therefore, this study aimed to determine the effect of fermentation duration on the antioxidant activity of strawberry kombucha and to identify the optimal fermentation duration for achieving the highest antioxidant activity. This study employed a quantitative research design using a laboratory experimental method. Strawberry kombucha was prepared from a mixture of fresh strawberries, water, granulated sugar, SCOBY starter solution, and SCOBY, followed by fermentation for 7, 10, and 13 days. Antioxidant activity was evaluated using the UV-Vis spectrophotometric method with DPPH reagent. The results demonstrated that fermentation duration significantly affected the antioxidant activity of strawberry kombucha. The highest antioxidant activity was achieved on day 10, with an IC50​ value of 24.69 ppm, which was categorized as very strong antioxidant activity. Fermentation on day 13 resulted in an IC50​ value of 30.69 ppm, which also fell within the very strong category, whereas fermentation on day 7 produced an IC50​ value of 74.38 ppm, categorized as strong antioxidant activity. Therefore, a fermentation duration of 10 days was identified as the optimal condition for producing the highest antioxidant activity. The findings of this study are expected to contribute to the development of beverage formulations rich in antioxidant compounds.